Design of a ZETA Converter Based MPPT Controller using PSO Algorithm for Renewable Energy Source Supplying DC Load - TM. Navinkumar; P. Puviya (Journal of Power Electronics and Devices, 2017)
The creation of power from renewable energy sources like wind energy has extended as of late because of ecological issues and the absence of ordinary energy sources in the future. Among all the renewable assets, wind power is the most well-known assets because of its simplicity of accessibility and its turn change into power. In this work, a basic technique for following the maximum power (MP) attainable in the wind energy conversion system (WECS) and nearby planetary group for direct current micro grid application is executed. A three stage diode bridge rectifier with a dc – dc converter (ZETA converter) has been utilized between the terminals of a wind driven induction generator and dc micro grid. The induction generator is being worked in a self-excited mode with provocation capacitor at stator. i.e., dc-grid voltage is considered as a control variable to track the MP in the forthcoming WECS. In this manner, the forthcoming calculation for maximum power point tracking (MPPT) is separate from the machine and wind-turbine particular. This strategy has been created for deciding the duty ratio of the dc–dc converter for the working of the forthcoming system in MPPT area utilizing wind turbine part, the consistent state indistinguishable circuit of an induction generator, and power value in power converters. The Circuit being simple and basic algorithm is the advantages of the proposed WECS. The effective working of the proposed technique for MPPT has been shown through the outcomes alongside the simulation values.